Da cor à chuva: direção de arte e identidade cultural em filmes paraenses - COSTA, Victória Ester Tavares da (2023)
Historical events and cultural expressions are strongly correlated, art is one of the parts at which this proximity is perceived. The following research aims to reflect about the image of the amazonian pierced by visual observation from the art direction. Visual film elements allow the dissemination and construction / replication of cultural identities of societies and theme of the story that is reported. Express themselves about their place of speech has been more present in Latin American’s productions, thus, revealing and rethinking of their own languages and identities, previously dominated by the direct influence of colonialism. Today there are still the chains with which we are familiar without notice, but the position is changing by the voice taking, reinventing our own language and aesthetics. Thus, by analizing three contemporary short films of Pará, we intend to understand the view that the amazonian has of itself and how it pierces on the screen.